Risk Analysis in Halal Fast Food Supply Chain Restaurant using Risk Map Method - Amalia, Putri; Handayani, Nurfitria; Apriza, Maeva; Kusrini, Elisa (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Halal food has increasing demand in recent years. Many countries are promoting its tourism and culinary by providing halal status. In order to implement Halal system which is used to obtain Halal status, the culinary or restaurant company should accomplish several requirements that covers from many stakeholders in their supply chain management such as supplier, logistics, and production process. Hence, there are some risks obtained in conducting Halal supply chain system. The risks found at this research are from its business process which is procurement, raw material delivery, inventory, production, and consumer. From those processes, the risks discovered are listed and assigned with their severity and probability, ended up in Risk Priority Index. The risks then ranked and mapped in the risk map in order to know which risks that has high impacts. Some responses are proposed to overcome the critical risks, such as sanitary checking before delivered to the customer, make some chambers, and make SOP related to hygiene of the kitchen.